MITOCHONDRIA AS PHARMACOLOGICAL TARGETS: THE DISCOVERY OF NOVEL ANTI-OBESITY MITOCHONDRIAL UNCOUPLERS FROM AFRICA’S MEDICINAL PLANTS - Ocloo, Augustine; Dongdem, Julius Tieroyaare (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Obesity results from prolonged positive imbalance between energy in take and expenditure. When food intake chronically exceeds the body’s energy need, an efficient metabolism results in the storage of the excess energy as fat. Mitochondria are the main centre for energy production in eukaryotic cells. Mitochondrial proton cycling is responsible for a significant proportion of basal or standard metabolic rate, therefore, further uncoupling of mitochondria may be a good way to increase energy expenditure and hence represent a good pharmacological target for the treatment of obesity. This implies that, any chemical agent or photochemical compound that further uncouples the mitochondria in vivo without having any effect on mitochondria activity could be a potential target in finding treatment for obesity. In the past, uncoupling by 2, 4-dinitrophenol has been used this way with notable success. This paper discusses the mitochondria as targets in the discovery of potential plant natural anti-obesity products from Africa’s rich rainforests